Nationwide In-hospital Mortality Following Pancreatic Surgery in Germany is Higher than Anticipated - Nimptsch, Ulrike; Krautz, Christian; Mansky, Thomas; Grützmann, Robert; Weber, Georg (Annals of Surgery, 2016)
We aimed to determine the unbiased mortality rates for pancreatic surgery procedures at the national level through a comprehensive analysis of every inpatient case in Germany.Several studies have proclaimed a general improvement of perioperative outcomes following pancreatic surgery. These results are challenged by recent analyses of large US databases that found strong volume-outcome relationships, with high mortality in low-volume facilities.All inpatient cases with a pancreatic surgery procedure code in Germany from 2009 to 2013 were identified from nationwide administrative hospital data. We determined the absolute number of patients and the in-hospital death rate for crucial subcategories such as medical indications and types of surgical procedure.A total of 58,003 inpatient episodes of pancreatic surgery were identified between 2009 and 2013. Annual case numbers increased significantly, which was primarily attributed to patients aged 70 years and older. The overall in-hospital mortality rate (10.1%) did not significantly change during the study period. Major pancreatic resections were associated with mortality ranging from 7.3% (distal pancreatectomy) to 22.9% (total pancreatectomy). Postoperative interventions indicative of severe complications were documented frequently (eg, more than 6 blood transfusions in 20% of all patients and relaparotomy in 16%). Their occurrence was associated with a dramatic increase in mortality.At the national level in Germany, perioperative mortality is higher than anticipated from previous studies. The absence of a significant reduction in overall mortality challenges current health policies that aim to improve the outcomes of high-risk surgical procedures in Germany.
EVALuna2:15249